Retinal Artery Occlusion: A Review of Current Management Practices - Hannah Yu; Sophia Choi; Rodney Guiseppi; Touka Banaee (Journal of Ophthalmic & Vision Research)
Retinal artery occlusion (RAO) is a well-characterized ischemic ophthalmic event that may result in sudden and devastating vision loss. The etiology of RAO may vary including both arteritic and non-arteritic causes and the location of the lesion can extend from the ophthalmic artery to the branches of the central retinal artery. Given this variable causes of RAO, the clinical presentation and extent of vision loss may also differ from case to case, necessitating a prompt and thorough evaluation, including a full stroke work up. While there is currently no widely accepted standard for the treatment of RAO, there are several proposed methods that have been or are currently being investigated through retrospective studies and prospective trials. The current article aims to provide a review of the pathophysiology, clinical presentation, and management of RAO in addition to presenting a systematic review of recently published studies on treatment options for RAO.